2020
DOI: 10.1002/eap.2156
|View full text |Cite
|
Sign up to set email alerts
|

Rare species of wood‐inhabiting fungi are not local

Abstract: Wood-inhabiting fungal communities are a diverse and ecologically critical part of forest ecosystems, yet the spatial structure of fungal biodiversity in these ecosystems is largely unknown. Legislation allowed harvesting of deadwood from temperate rainforests on conservation lands in New Zealand following Cyclone Ita in 2014. Harvesting guidelines specified widely spread harvesting, on the assumption that rare fungal species may be highly spatially restricted, but were not based on quantitative assessment. We… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
2
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 53 publications
(73 reference statements)
3
2
0
1
Order By: Relevance
“…These rare species might be mainly specialists, i.e., tree species-specific, as demonstrated by Moor et al [74]. Such hypotheses highlight the existence of many rare species in deadwood [75,76] and the importance of tree species diversity to promote the global diversity of fungi in forest ecosystems [77]. Thus, our findings suggested that rare fungal species are largely involved in community dissimilarities, as already mentioned in Thorn et al [78].…”
Section: Discussionsupporting
confidence: 82%
“…These rare species might be mainly specialists, i.e., tree species-specific, as demonstrated by Moor et al [74]. Such hypotheses highlight the existence of many rare species in deadwood [75,76] and the importance of tree species diversity to promote the global diversity of fungi in forest ecosystems [77]. Thus, our findings suggested that rare fungal species are largely involved in community dissimilarities, as already mentioned in Thorn et al [78].…”
Section: Discussionsupporting
confidence: 82%
“…This means that, biologically, sites relatively close together (under 1 km) and within the same habitat and edaphic type often had very different fungal communities, as evidenced by their high levels of turnover. Similar results were seen in fungal communities colonizing decaying wood both following a storm on the west coast of the South Island (Dickie et al 2020) as well as in a Bavarian forest in southeastern Germany (Müller et al 2020), and root endophytes in Europe (Glynou et al 2016), suggesting a lack of strong distance effects for fungal communities may be a general pattern, at least in temperate ecosystems. This may reflect strong assembly history or priority effects (Fukami et al 2010, Fukami 2015.…”
Section: Distance Effectssupporting
confidence: 56%
“…2012, Dickie et al. 2020]). At this scale, fungal communities, like most other systems, often have have strongly uneven species‐abundance relationships that are usually log‐normal or Pareto shaped (Dumbrell et al.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…A A (Sintes et al, 2015;Raes et al, 2018b), B A (Amend et al, 2013;Sul et al, 2013;Wang and Soininen, 2017;Raes et al, 2018b), F A (Raes et al, 2018b), F T (Tedersoo et al, 2014;Cox et al, 2016;Ogwu et al, 2019) B T (Nemergut et al, 2011;Green et al, 2016;Stopnisek and Shade, 2020), A A (Zhou et al, 2019;Liu J. et al, 2020), B A (Pommier et al, 2007;Humbert et al, 2009;Östman et al, 2010;Nemergut et al, 2011;Liu et al, 2015;Bienhold et al, 2016;Liao et al, 2017;Mo et al, 2018), B T (Nemergut et al, 2011;Valverde et al, 2014;Ji et al, 2020), F T (Zhang et al, 2018;Gange et al, 2019;Dickie et al, 2020) F T (Helander et al, 2007;Botnen et al, 2019) F T (Tedersoo et al, 2010(Tedersoo et al, , 2012(Tedersoo et al, , 2014Timling et al, 2012;Holt et al, 2015;Glynou et al, 2016;Pärtel et al, 2017;de Menezes et...…”
Section: Organismal (Physiological)unclassified